Is Airborne 2,4,6-Trichloroanisole (TCA) a Threat for Bottled Wine? - Andrii Tarasov; Rainer Jung (Australian Journal of Grape and Wine Research)
Background and Aims. This work investigated the TCA permeability of twelve types of commercial bottle closures during 24 months of bottle storage in the d5-TCA-contaminated atmosphere: medium pollution (max. ∼50 ng/L of d5-TCA in the air) and high pollution (max. ∼500 ng/L of d5-TCA in the air). Methods and Results. The d5-TCA content of wine samples and bottle closures was monitored by GC-MS analysis, and the closures of one group (comprising natural corks, agglomerated stoppers, and BVS Tin Saran™ screw caps) were found to be excellent barriers against airborne d5-TCA, i.e., no contaminant was detected in wine under any storage conditions. In contrast, a second group of closures (synthetic stoppers with low OTR, BVS Saranex™, and plastic body screw caps) allowed permeation of d5-TCA, polluting the wine when air contamination was high, albeit no d5-TCA was detected in wines following storage under medium air contamination conditions. A third group of closures (synthetic stoppers with medium and medium + OTR, MCA screw caps, and glass stoppers) allowed d5-TCA to accumulate in wine under both medium and high contamination environments. Conclusions. Some commercial bottle closures were found to permeate airborne d5-TCA, thereby contaminating bottled wine under certain storage conditions. Significance of the Study. This work provides the wine industry with insight into the potential for postbottling contamination of wine by airborne TCA.